Determination of Copper and Zinc Content in Soil Based on Soil Position and Depth in Palm and Rambutan Garden Area - Perangin Angin, Elsa Sucita; Chairuddin (Journal of Chemical Natural Resources, 2022)
The determination of copper and zinc in soil based on the position and depth at the application land of palm oil in the Rambutan garden. Part of control land, between rorak and plant, and rorak at a depth of 0-20 cm, 20-40 cm and 40-60 cm. Each 3 g soil sample was destructed with 10 mL of HNO3 concentrated at 180ÂºC for 20 minutes. Cu and Zn's content was determined using Atomic Absorption Spectroscopy (AAS) at wavelength 324.7 nm andÂ  213.9 nm, respectively. The analysis shows that Cu and Zn metal increase rorak at 84.0% and 57.7%, and soil between rorak and plant at 76.9% and 42.4%.